IMPLEMENTATION OF GEOGRAPHY CURRICULUM AND LEARNING METHODS: A BIBLIOMETRIC ANALYSIS - Nugroho, Albertus Erico Jerry Krisna; Sugiyanto, Sugiyanto; Prihadi, Singgih (Universitas Labuhanbatu, 2025)
Purpose – This study examines the execution of the geography curriculum and pedagogical strategies through a bibliometric analysis technique. By utilizing data from the Scopus database, the research identifies publication trends, thematic clusters, and key factors influencing the development of geography education.Methodology – This research uses a bibliometric analysis approach using data from the Scopus database. The analysis employed VOSviewer to visualize co-occurrence networks and bibliographic coupling. Thematic clusters were identified to map research directions, authorship collaboration, and methodological developments in geography education.Findings – The findings identify five primary study clusters: (1) curriculum implementation in geography education, (2) methodologies for geography learning, (3) academic performance and evaluation, (4) citizenship-oriented learning development, and (5) international curriculum execution. Innovative methods such as project-based learning and integrating Geographic Information Systems (GIS) are among the most frequently discussed strategies. The study also highlights challenges such as gaps between curriculum planning and implementation, limited infrastructure, and the need for teacher training.Contribution – Using a bibliometric approach, this study provides a comprehensive overview of trends and directions in implementing geography learning curriculum and methods. The findings provide a basis for designing more effective educational policies and valuable insights for future research development.